ANALISIS EKSKLUSI DAN INKLUSI PADA BERITA MISTERI TEWASNYA BRIGADIR JOSUA, FAKTA BARU TERUNGKAP, BHARADA E MENGAKU DIPERINTAH MEMBUNUH BERDASARKAN MODEL THEO VAN LEEUWEN - Eulis Nurhaeti; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Today's phenomena or events regarding ideology, politics, economy, society, culture, and law can easily be known through print or electronic mass media coverage. The objectives of this research are: 1) to determine who is marginalized by the Bangka pos.com mass media in their coverage of the Mystery of Brigadier Josua's death, New Facts: Bharada E Admits to Being Ordered to Kill, and 2) to analyze the language strategies used based on Theo Van Leeuwen's Critical Discourse Analysis model. The research method employed in this study is descriptive. The research objects are news texts regarding the murder of Brigadier Josua in online mass media outlets, specifically Bangka pos.com on August 8, 2022, and epanrita.net on Monday, August 8, 2022. The findings of the two news articles indicate that the content of the Bangka pos.com news marginalizes Bharada E as the murderer of Brigadier Josua. The content of the news article on epanrita.net on August 8, 2022, titled "Revealed! Bharada E's Confession: Ordered by Superiors to Kill Brigadier J," marginalizes Bharada E as well but introduces another actor that suggests Bharada E is no better than Brigadier Ricky Rizal. Based on the data above, it can be concluded that discourse operates to define something, legitimize something, and blame others. Keywords: exclusion, inclusion, Theo Van Leeuwen's model